THE IMPORTANCE OF COMMUNICATIVE STRATEGIES IN THE COMMUNICATION OF FUTURE PRIMARY SCHOOL TEACHERS - Izbosarova Zuhra (PT. Antis International Publisher, 2024)
In this article, the communicative skills of future elementary school teachers are an important tool for the successful organization of the educational process, its components, the concepts of identification and reflection as concepts that determine the effectiveness of communication, the use of communicative strategies to improve interactions at school, the importance of effective problem solving, strengthening of trust and cooperation, improving the educational process in achieving the overall success of students is highlighted